PERENCANAAN KONSTRUKSI BETON SLIPWAY - 150 LWT - Dharma, Budhi (Gema Teknologi, 2011)
Budhi Dharma, in paper Construction Planning of Slipway - 150 LWTÂ  Concrete explain that in shipyard planning major facility types shipyard slipway suitable transverse system was built in the open or closed.To ship with 150 tons LWT according to the register BKI got main dimension vessels = 34 meters LOA,30 meters LP, 6 meters B, the ship draft T = 2,2 meters, and empty vessel draft Tk = 1,18 meters and block coefficient = 0,68.Of the main dimension of the vessel were then long slipway, heavy lorries and heavy lorries transfer launchers after the total weight is obtained the dimensions of the placement of concrete beam rail and lorry.Keyword : Slip way and structure concrete